Development of resistance to antibiotics in bacteria Staphylococcus spp. Isolated from milk samples in the sheep breedings on east of Slovakia - Milan Vasiľ (Potravinarstvo, 2018)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:Ls